THE ENVIRONMENTAL ATLAS OF THE CORUMBATAI WATERSHED - SP, BRAZIL - Garcia, Gilberto J.; Antonello, Sergio L.; Magalhães, Mônica G.M. (Revista Brasileira de Cartografia, 2009)
The Corumbatai watershed (1.710 km2 ) in the State of São Paulo - Brazil, is a well known region, mainly because oneof the branches of the São Paulo State University - UNESP is located there, where most of the departments are relatedon environmental sciences. However all available data are in the analogical format and stored in different libraries anddepartments, which means that they are not as useful as they could be, not only for the University, but mainly for thesociety. The project followed four steps: 1 - Data Identification and Collection, 2 - Data Completion, 3 - DataPreparation and 4 - Data Input/Multimedia Programming. The Environmental Atlas is structured as follows:PRESENTATION; LOCALIZATION; ABIOTIC ENVIRONMENT: Geology, Geomorphology, Pedology,Climatology, Hydrology; BIOTIC ENVIRONMENT: Natural Vegetation, Forestry and crops, Fauna; SOCIOECONOMY;PHOTOGRAPHIC COLLECTION; WORKING TEAM. All information was integrated through theFLASH 5 (Macromedia) multimedia software. The final product is available at the IGCE-UNESP's websitewww.rc.unesp.br/igce/ceapla/atlas .